2015
DOI: 10.1080/17550874.2015.1010188
|View full text |Cite
|
Sign up to set email alerts
|

The impact of red deer on liverwort-rich oceanic heath vegetation

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Conversely, the lack of response to light in the least disturbed (N) treatment suggests that the dense canopy cover is restricting species with greater light requirements. This is in keeping with the responses about individual species noted earlier, and especially the bryophyte and lichen responses (Burch, ; Harris et al, ; Moore & Crawley, ; Moore & Crawley, ,b; Virtanen & Crawley, ).…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, the lack of response to light in the least disturbed (N) treatment suggests that the dense canopy cover is restricting species with greater light requirements. This is in keeping with the responses about individual species noted earlier, and especially the bryophyte and lichen responses (Burch, ; Harris et al, ; Moore & Crawley, ; Moore & Crawley, ,b; Virtanen & Crawley, ).…”
Section: Discussionsupporting
confidence: 86%
“…Flagmeier et al (2014) found a significant decline of S. nimbosa over 50 year period in oceanic-montane liverwort heath in Scotland, with grazing, eutrophication and warmer and drier conditions as the potentially most important drivers of the change. Decline of the oceanic liverwort species (S. nimbosa included) was also found by Moore and Crawley (2015) who studied the impact of red deer. However in Norwegian localities decreased grazing is do the field work in good enough weather.…”
Section: Habitat Limitation and Conservationmentioning
confidence: 62%